Stranger in a strange land: genetic variation of native insect resistance biomarkers in UK Sitka spruce (Picea sitchensis [Bong.] Carr.). (30th March 2021) - Tumas, Hayley R; Soufi, Ziad; Woolliams, John A; McLean, J Paul; Lee, Steve; Cottrell, Joan E; Ilska, Joanna J; Lopez, Gustavo; MacKay, John
Abstract: Reforestation in the British Isles (UK and Ireland) has been dominated with the use of an exotic conifer tree species, Sitka spruce ( Picea sitchensis [Bong.] Carr.). Sitka breeding in the UK was developed from a single provenance, the Haida Gwaii Islands (Canada), which is both well suited to the British climate and highly susceptible to the white pine weevil ( Pissodes strobi L.) in its native range. We examined variation and heritability of insect resistance related traits and assessed potential trade-offs with tree growth in 50 full-sibling families and 13 clonally replicated genotypes growing in the UK. We measured bark levels of three terpenes (dehydroabietic acid, (+)-3-carene and terpinolene) shown to confer resistance to the white pine weevil in Sitka spruce's native range, on the principle that these defence compounds may also contribute to pest resistance in the UK. We compared our results with published findings from the native range and also used individuals from a Haida Gwaii seed lot grown in the UK for comparison of terpene levels. Dehydroabietic acid content in the UK breeding population was similar to populations from resistant native populations, but (+)-3-carene and terpinolene levels were relatively low. Narrow sense heritability for dehydroabietic acid, (+)-3-carene and terpinolene was estimated as 0.20, 0.93 and 0.98, respectively from the full-sib data, and this evidence of genetic variance was supported by estimates of broad sense heritability from the smaller clonal study. Terpene content was found to be positively correlated to growth traits. The heritability estimates and genetic correlations indicate that selective breeding should be effective in raising levels in the UK breeding population of the three candidate terpenes implicated in weevil resistance. However, low levels observed indicate that other provenances from the native range may produce greater short-term improvements for two of the terpenes.